2019
DOI: 10.1177/1042258719883995
|View full text |Cite
|
Sign up to set email alerts
|

Contagion of Entrepreneurial Passion: Effects on Employee Outcomes

Abstract: This article analyzes the contagion process of entrepreneurial passion and its effects on employee outcomes. We develop a mediation model showing entrepreneurs’ entrepreneurial passion affects an employee passion response, which in turn affects employee outcomes. We draw on a dual-process perspective to analyze how entrepreneurs’ emotional and identity displays interact to create employees’ perceptions of entrepreneurs’ passion, and question whether the contagion effect uniformly works for all employees. Our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 100 publications
(205 reference statements)
5
45
0
Order By: Relevance
“… Cardon et al (2017) suggested that entrepreneurial passion motivates people to spot innovative opportunities and develop a new business intention. Similarly, Hubner et al (2019) stated that entrepreneurial passion is the crucial factor for achieving motivation and success and is important in predicting entrepreneurial intention. Karimi (2020) examined the direct role of entrepreneurial passion and the mediating effect of the theory of planned behavior using 310 Iranian public university students’ data from different courses.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“… Cardon et al (2017) suggested that entrepreneurial passion motivates people to spot innovative opportunities and develop a new business intention. Similarly, Hubner et al (2019) stated that entrepreneurial passion is the crucial factor for achieving motivation and success and is important in predicting entrepreneurial intention. Karimi (2020) examined the direct role of entrepreneurial passion and the mediating effect of the theory of planned behavior using 310 Iranian public university students’ data from different courses.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In response to the growing interest in the changing context of knowledge work and the increase in alternative work arrangements (Hubner et al, 2020;Spreitzer et al, 2017), the present study emphasizes the importance of EPI in the development of work engagement in diverse knowledge work contexts. There is a positive gain cycle between antecedent determinants and the consequent outcomes of work engagement (Hakanen et al, 2008;Tims and Bakker, 2010), which makes work engagement such a significant element in worker wellbeing.…”
Section: Discussionmentioning
confidence: 97%
“…Schneider et al (2018) have established that organizational practices strongly correlate with workforce engagement, and Hubner et al (2020) have explained that experiencing meaningfulness in work leads to identifying with the (entrepreneurial) firm and building affective commitment. These ideas are in line with the concept of intrapreneurship (Moriano et al , 2014) and can lead to entrepreneurial types of contributions (Hubner et al , 2020) in the employing organization. With the assistance of passionate and engaged employees, the chances of tackling the challenges of the fast-paced contemporary economy and gaining a competitive advantage become more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being passionate about entrepreneurship in general may be a catalyst in starting a company. As a result, individuals who are passionate about an entrepreneurial career are likely to build up an intention to start a company (Chen et al 2009 ; Miller et al 2012 ; Santos and Cardon 2019 ; Hubner et al 2019 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%